2014
DOI: 10.1212/wnl.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

PDE5 inhibition alleviates functional muscle ischemia in boys with Duchenne muscular dystrophy

Abstract: Objective: To determine whether phosphodiesterase type 5 (PDE5) inhibition can alleviate exercise-induced skeletal muscle ischemia in boys with Duchenne muscular dystrophy (DMD). Methods:In 10 boys with DMD and 10 healthy age-matched male controls, we assessed exerciseinduced attenuation of reflex sympathetic vasoconstriction, i.e., functional sympatholysis, a protective mechanism that matches oxygen delivery to metabolic demand. Reflex vasoconstriction was induced by simulated orthostatic stress, measured as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 29 publications
1
84
0
3
Order By: Relevance
“…The reported reduced recruitment of sufficient blood flow in patients with BMD during muscle activity responsible for relative ischemia [37] is improved by PDE5 inhibition in some studies [22,38,39], but not in all of them [23,24], which may relate to variations in methods applied. Corresponding reduced brain blood flow recruitment during activation was hypothesized to be present in patients with BMD and restored by PDE5 inhibition; the current data partly support this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…The reported reduced recruitment of sufficient blood flow in patients with BMD during muscle activity responsible for relative ischemia [37] is improved by PDE5 inhibition in some studies [22,38,39], but not in all of them [23,24], which may relate to variations in methods applied. Corresponding reduced brain blood flow recruitment during activation was hypothesized to be present in patients with BMD and restored by PDE5 inhibition; the current data partly support this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…The administration of Tadalafil or Sildenafil resulted in beneficial effects in mdx mice and DMD patients [19,49,50]. Unfortunately, disappointing results came out on February 2016 from the phase III trial of Tadalafil, due to failure to prove evidence for efficacy in slowing the decline in the walking ability of DMD boys.…”
Section: Alternative Approachesmentioning
confidence: 99%
“…This is unfortunate because it would have been of great interest to follow the cardiac status of those patients as they approached the age of onset of cardiac symptoms, had they remained on the drug. The anticipated mechanism in the ambulatory trial, suggested by a combination of animal and human studies, 12,42,43 was to improve blood flow to exercising leg muscles by amplifying deficient nitric oxide signaling to vascular smooth muscle, thus preventing ischemia and preserving muscle. Although our dog studies did not focus on skeletal muscle function, we examined histology of diaphragm and quadriceps muscles from treated and untreated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafil restores limb functional sympatholysis in patients with Becker muscular dystrophy 11 and DMD. 12 Based on these muscle benefits, a phase III clinical trial for the use of tadalafil in DMD was performed in patients exhibiting normal cardiac function (ClinicalTrials.gov identifier NCT01865084). Consequently, the impact of long-term PDE5 inhibition on the progression of cardiomyopathy in DMD is a topic of high and immediate clinical significance.…”
mentioning
confidence: 99%